PERBEDAAN DAN HUBUNGAN TINGKAT KOLEKTIVISME DENGAN MOTIVASI KERJA WISUDAWAN FAKULTAS EKONOMIKA BISNIS DAN FAKULTAS ILMU BUDAYA UNDIP - Danimarcha, Adlin Rizki; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the differences in the level of collectivism with graduate work motivation and relationships collectivism a variable component of motivation include: salaries, social work, and achievement. The sample used in this study were graduates of the Faculty of Economics and Business (FEB) and the Faculty of Humanities (FIB). As the independent variable is the individualism-collectivism, gender, and type of education. While the dependent variable is the motivation include: salaries, social work, and achievement. Sample method used in this study is simple random sampling. Methods of data collection using questionnaires distributed to 167 respondents. Engineering test data used penelittian include normality test charts, test the validity of the R arithmetic and R tables, test reliability by using coefficient alpha (Cronbach's alpha), and a different test T-test is to determine whether there is a difference in variance and correlation Karl Pearson to investigate the association between variables. Results of the analysis and discussion of the revelation that: (1) There are differences in the level of collectivism in work motivation graduates FEB and FIB, (2) there is a relationship between the level of collectivism in salary desired graduates, (3) there is a relationship between the level of collectivism in the social environment of work expected of graduates , (4) there is a relationship between the level of collectivism on the achievements of the coveted graduates.